TENSION FORCE EQUALIZER IN A ROPE SYSTEM USING A PROXIMITY SENSOR - Leopold HRABOVSKÝ (Scientific Journal of Silesian University of Technology. Series Transport)
Different values of tension forces in the load-bearing ropes of elevators, which push the rope into the grooves of the traction discs with different pressure, are the cause of uneven wear of the grooves of the traction discs under operating conditions. Current technical standards in the EU stipulate that the load suspended on load-bearing ropes be evenly distributed to all ropes used, using one of the many construction designs for tension force equalizers in the rope system. The main subject and primary objective of this paper are to present the construction design, 3D model and produced device of one of four produced prototypes, which were constructed in the “Research and Testing Laboratory”, and allow setting of differing values of tension forces in the system of ropes of a traction elevator, to values of the same size. Laboratory measurements were performed on the produced device, which enables the detection of tension forces in ropes and the magnitude of these forces in the required period to be graphically displayed on a PC. The prototype tension force equalizer can show the functionality and practical applicability of the procedure of balancing the levels of tension forces, which are of unequal strengths at the start of the laboratory measurement.